Albumin-corrected Total/Ionized Calcium Ratio is not Superior to Total/Ionized Calcium Ratio as an Indicator of Citrate Accumulation. Issue 11 (November 2017) - Zheng, Yin; Zhuang, Feng; Zhu, Qiuyu; Ma, Shuai; Xu, Yao; Lu, Jianxin; Hao, Guihua; Gu, Yong; Hao, Chuanming; Zhu, Mingli; Ding, Feng
Background: Total/ionized calcium ratio has been used as an indirect index of increased plasma citrate concentration during citrate anticoagulation. However, they were obtained without any adjustment of total calcium for albumin. Herein, we investigated whether the albumin-corrected total/ionized calcium ratio performed better than total/ionized calcium ratio. Methods: 20 critically ill patients were treated with continuous venovenous hemofiltration (CVVH) using citrate anticoagulation. The systemic total, ionized calcium and albumin levels were dynamically measured, and correlations between different calcium parameters and plasma citrate levels were analyzed. Results: The highest correlation was found between plasma citrate level and total/ionized calcium ratio at the third hour (R = 0.88, p<0.001). The albumin-corrected total/ionized calcium ratio was not superior to total/ionized calcium ratio. Conclusions: The total/ionized calcium ratio at the third hour after the start of citrate-CVVH is an early and simple indicator to reflect increased plasma citrate level. Adjustment of systemic total calcium for serum albumin is not necessary.